PELAKSANAAN PENDIDIKAN POLITIK OLEH DPD PARTAI GERINDRA JAWA TIMUR DALAM RANGKA MENGHADAPI PEMILU SERENTAK 2019 (Studi Pada DPC Partai Gerindra Kabupaten dan Kota Mojokerto) - Halimur Rosyid (LPPM UNISDA, 2019)
General election Simultaneously 2019 is a challenge and opportunity for all elements of the nation in improving the political system and democracy in Indonesia, that is the reason that became the basis of the East Java Gerindra Party to carry out political education in Mojokerto. This study aims to describe the implementation of political education for three times with qualitative descriptive methods and interactive analysis. The results of this study reveal that the objectives and material presented in the implementation of political education are still oriented towards strengthening internal party institutions as an effort to strengthen ideology, winning strategies and internal party consolidation. In addition, the obstacles that arise are methods of inappropriate communication and limited time of activity.